Report on the situation of youth in selected Caribbean countries (ECLAC [Port of Spain]TT, 2007)
Analyzes the status of youth in a number of Caribbean and Latin American countries in terms of education, employment and, sexual and reproductive health using available 2000 census data.
Keywords: YOUTH